Rescuing the Knee: Arthroscopic Extraction of a Long-neglected Glass Fragment - Anil Kumar Gulia; Sanjeev Kumar; Mohit Sharma; Prabhat Mittal; Rakesh Kumar (Journal of Orthopedics, Traumatology and Rehabilitation)
The knee joint frequently encounters penetrating injuries and has ample space to harbor foreign objects. This case study delves into the experience of a 22-year-old male who suffered persistent pain due to a neglected foreign object in his knee joint. After its arthroscopic removal, a complete resolution of symptoms was achieved. It highlights the importance of prompt arthroscopic intervention for optimal outcomes. Arthroscopy stands as the favored minimally invasive method for extracting foreign bodies from the knee joint, especially from its deeper and less accessible regions.